Residential Fire in Malaysia, April 2026: An Analysis of Its Impacts on Coastal Ecosystems, Air Quality, and Public Health - Nadiyah Zaskia Farida; Nia Dwinta; Ririn Oktavia; Siti Nursyahrani (Journal of Social Science and Humanities, 2026)
Residential fires constitute one of the major disasters that generate multidimensional impacts on social, economic, public health, and environmental systems. In April 2026, a large-scale residential fire occurred in Kampung Bahagia, Sabah, Malaysia, destroying approximately 1,000 houses and leaving thousands of residents displaced. This study aims to analyze the impacts of the fire on coastal ecosystems, air quality, and public health from an environmental ecology perspective. The research employed a qualitative descriptive approach through a literature review, utilizing secondary data obtained from scientific articles, peer-reviewed journals, fire incident reports, and other relevant supporting documents. The findings indicate that the fire contributed to the contamination of the coastal environment through the deposition of combustion residues, including ash, charcoal, heavy metals, and synthetic materials, into adjacent water bodies, thereby posing potential threats to ecological balance. Furthermore, the fire emitted significant air pollutants, including particulate matter (PM₂.₅ and PM₁₀), carbon monoxide (CO), nitrogen oxides (NOₓ), sulfur dioxide (SO₂), and polycyclic aromatic hydrocarbons (PAHs), resulting in deteriorated air quality and an increased risk of adverse health outcomes, particularly acute respiratory infections (ARI), asthma, bronchitis, and eye irritation. The study further reveals that the vulnerability of coastal settlements to residential fires is strongly influenced by high housing density, the widespread use of combustible building materials, and the limited availability of fire mitigation systems and emergency response infrastructure. Therefore, strengthening disaster risk reduction strategies, enhancing community preparedness and resilience, improving spatial planning in coastal areas, and implementing continuous environmental quality monitoring are essential to reducing the likelihood and impacts of similar incidents in the future.